Peningkatan Modularitas Sistem Tata Kelola Perkuliahan Dengan Pendekatan Model View Controller - Adi Chandra Syarif (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2020)
Based on PP No. 4 year 2014, college is a unit of organized higher education. In Providence, the College has the autonomy to manage their own institution comprising the system setting, planning, supervision, monitoring, and evaluation to achieve the goals of higher education. Atma Jaya University Makassar (UAJM) as one of the higher education has been harnessing information and communication technology infrastructure such as SIAMIK and other supporting systems. The Lecture Process Management System is a support system that has been developed. This system is part of the supervision system of the lecture at Atma Jaya University Makassar. Based on the results of the simulation test, it was found that the service interface of the Lecture Management System tablet PC was still difficult to use due to the coding structure carried out and the involvement of different teams. This study aims to update the data structure and interface of the java platform for the services of the Lecture System on the tablet PC system, update the audio and video data acquisition modules and engineer interaction services on the lecture digital attendance module. The development method used is the waterfall design approach with the UML method. System reengineering methods are used to understand the system and concept of the Model-View-Controller architecture that encapsulates data along with processing (model), isolates it from the manipulation process (controller) and display (view) to be represented on a user interface. The results of the research are that the system that has been reengineered and integrated with SIAMIK can help lecturers and chairman of the study program in planning, implementing and supervising student academic activities at FTI-UAJM.